2020
DOI: 10.1097/gox.0000000000002970
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Repair of Traumatic Iliac Crest Flank Hernias with Mesh Strips

Abstract: Background: Traumatic abdominal wall hernias are rare injuries resulting from blunt abdominal trauma. Traditional approaches have included both open and laparoscopic approaches, with placement of large meshes with giant overlaps. Perhaps the most technically difficult aspect of these repairs is fixating the abdominal wall to the iliac crest. The senior author has developed a method of repair using 2-cm strips of mesh. In this article, we present a description of 4 patients treated with this techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…According to another report on 107 mesh sutured repairs of abdominal wall defects published in 2016 [22], the recurrence rate (early mean follow-up time of 234 days) was < 4%, and the incidence of surgical site occurrence (infection, seroma, hematoma, reoperation, delayed wound healing) was 17%. Another study published in 2020 reported that among four patients with traumatic flank hernia who underwent mesh strip repair [6], there were no complications such as surgical site infection, hematoma, or wound breakdown and no recurrence during…”
Section: A a B Bmentioning
confidence: 99%
See 4 more Smart Citations
“…According to another report on 107 mesh sutured repairs of abdominal wall defects published in 2016 [22], the recurrence rate (early mean follow-up time of 234 days) was < 4%, and the incidence of surgical site occurrence (infection, seroma, hematoma, reoperation, delayed wound healing) was 17%. Another study published in 2020 reported that among four patients with traumatic flank hernia who underwent mesh strip repair [6], there were no complications such as surgical site infection, hematoma, or wound breakdown and no recurrence during…”
Section: A a B Bmentioning
confidence: 99%
“…The most important outcome in hernia repair is the recurrence rate. Table 1 summarizes 18 case series regarding lumbar hernia (including flank hernia) repair targeting a total of 526 patients reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. An open approach was performed in 13 studies, a laparoscopic approach in three studies, a combination of both approaches in one study, and a laparoscopic or robotic approach in one study.…”
Section: A a B B A A B Bmentioning
confidence: 99%
See 3 more Smart Citations